APOB‐associated cholesterol deficiency in Holstein cattle is not a simple recessive disease. (18th June 2019) - Häfliger, Irene Monika; Hofstetter, Sonja; Mock, Thomas; Stettler, Manuela Hanna; Meylan, Mireille; Mehinagic, Kemal; Stokar‐Regenscheit, Nadine; Drögemüller, Cord
Summary: In 2015, cholesterol deficiency (CD) was reported for the first time as a new recessive defect in Holstein cattle. After GWAS mapping and identification of a disease‐associated haplotype, a causative loss‐of‐function variant in APOB was identified. CD‐clinically affected APOB homozygotes showed poor development, intermittent diarrhea and hypocholesterolemia and, consequently, a limited life expectation. Herein, we present a collection of 18 cases clinically diagnosed as CD‐affected APOB heterozygotes. CD‐clinically affected heterozygotes show reduced cholesterol and triglyceride blood concentrations. The differences in total blood cholesterol and triglycerides between nine CD‐clinically affected and 36 non‐affected heterozygotes were significant. As only some APOB heterozygotes show the clinical CD phenotype, we assume that the penetrance is reduced in heterozygotes compared to the fully penetrant effect observed in homozygotes. We conclude that APOB ‐associated CD represents most likely an incomplete dominant inherited metabolic disease with incomplete penetrance in heterozygotes.